Internet Search Volume and Stock Return Volatility: The Case of Turkish Companies - Turan, Semen Son (Information Management and Business Review, 2014)
This study analyzes the relationship of the volatility ofstock returns and internet search volume (ISV). The dataset consists of 10 Turkish companies listed on the BIST-100 Index of Borsa Istanbul, and encompasses the period between January 2004 - September 2013. The GARCH (1,1) model is applied with two alternative mean specifications. The use of the novel exogenous variable ISV as proxy for investor sentimentis complemented through the inclusion of trading volume.Results show that as the GARCH (1,1) model becomes increasingly nested, volatility persistence declines with however no case of a vanishing G(ARCH) effect.